Nutrition cards developed by ILRI and partners adopted by Government of Rwanda in its own community health workers curriculum - CGIAR Research Program on Livestock (2020)
Government of Rwanda adopted nutrition cards developed by ILRI and partners (through a Feed the Future Innovations Lab for Livestock Systems research project) in its own community health workers curriculum.